Ciri khas Bugis dan segala keunikannya - Femas, Anis (Maliki Interdisciplinary Journal, 2024)
This article was created by the author to discuss some of the characteristics of Bugis and its uniqueness. Especially in the context of culture, the philosophy of life of the Bugis people, wedding customs, the tradition of sigajang laleng lipa or sarong fighting, the custom of mappalette’ bola or moving house in the Bugis tribe style, Bugis traditional clothing and the Bugis tribe’s habit of migrating using traditional boats, namely phinisi. This article also discusses the Bugis tribe, a community of people who live in the archipelago and have a variety of unique languages, arts and cultures. The Bugis tribe, whose center is in South Sulawesi, is also spread across various other islands, both in the archipelago and abroad, all of which are influenced by the habits of the Bugis tribe itself who like to sail and migrate. The Bugis tribe has unique characteristics and is rich in cultural values, therefore the cultural wealth of the Bugis tribe should be maintained and preserved because this is part of Indonesia’s diverse cultural identity. So this article can provide a deep insight into the cultural diversity of the Bugis tribe in Indonesia.